Determining the Effect of Financial Products and Service Delivery on Performance of Micro and Small Enterprises in Kisumu County, Kenya - Ouya, Joyce Obiero; Otieno, Simeyo; Baraza, Edwins (International Journal of Recent Research in Commerce Economics and Management (IJRRCEM), 2024)
The objective of this study was to determine the effect of financial products and service delivery on performance of micro and small enterprises in Kisumu County. This study used Transaction costs and Grameen Model theories which support independent variable. This research was conducted in Kisumu County, where 15,000 Micro and Small Enterprises owners were targeted by use of stratified random sampling from, different trading sectors which included; boda-boda operators, green grocers, cereals sellers. Second-hand clothes dealers, front door tailors, salonists and barbers. Sample size of 375 MSEs was arrived at by use of the Krejcie and Morgan formula and table to represent the whole population. Self- administered structured questionnaires and interview schedules were used to collect primary data which were therefore distributed to the respondents in Kisumu County. The study therefore used Descriptive survey research design. Data collected were organized in tables then analysed using Statistical Package for Social Sciences (SPSS) Version 27. The research instruments’ reliability was tested by use of Cronbach’s Alpha and the coefficient was found to be 0.7 which was accepted. Multiple linear regression model, Karl Pearson’s correlation and ANOVA were used in data analysis. The study concluded that good public image of the business depended on excellent business - customer relationship and service delivery to the customers which also leads to customer loyalty and retention by the business. The study recommended that MSE owners should buy their own means of transport to cut down on transportation expenses and uphold high business – customer relationship through good service delivery for better performance and growth.
Keywords: Micro and Small Enterprises; Financial Products; Service Delivery; Financial Inclusion